The electronic properties of doped single walled carbon nanotubes and carbon nanotube sensors - Tetik, E. (Condensed Matter Physics, 2014)
We present ab initio calculations on the band structure and density of states of single wall semiconducting carbon nanotubes with high degrees (up to 25%) of B, Si and N substitution. The doping process consists of two phases: different carbon nanotubes (CNTs) for a constant doping rate and different doping rates for the zigzag (8, 0) carbon nanotube. We analyze the doping dependence of nanotubes on the doping rate and the nanotube type. Using these results, we select the zigzag (8, 0) carbon nanotube for toxic gas sensor calculation and obtain the total and partial densities of states for CNT (8, 0). We have demonstrated that the CNT (8, 0) can be used as toxic gas sensors for CO and NO molecules, and it can partially detect Cl₂ toxic molecules but cannot detect H₂S. To overcome these restrictions, we created the B and N doped CNT (8, 0) and obtained the total and partial density of states for these structures. We also showed that B and N doped CNT (8, 0) can be used as toxic gas sensors for such molecules as CO, NO, Cl₂ and H₂S. Представлено ab initio обчислення зонної структури та густини станiв напiвпровiдникових вуглецевих
нанотрубок з однiєю стiнкою, що володiють високими ступенями (аж до 25%) замiщення B, Si i N. Процес
легування складається з двох етапiв, а саме, рiзнi вуглецевi нанотрубки для сталої швидкостi легування та
рiзнi швидкостi легування для зигзагоподiбної (8, 0) вуглецевої нанотрубки. Проаналiзовано залежнiсть
легування нанотрубок вiд швидкостi легування i вiд типу нанотрубки. На основi цих результатiв вибрано
зигзагоподiбну (8, 0) вуглецеву нанотрубку для обчислення датчика токсичного газу та отримано повнi i
парцiальнi густини станiв вуглецевих нанотрубок (8, 0). Показано, що вуглецева нанотрубка (8, 0) може
бути використана в якостi датчикiв токсичних газiв для молекул CO i NO; вона здатна частково виявляти
токсичнi молекули Cl₂, але не здатна виявляти H₂S. Щоб подолати цi обмеження, створено B i N леговану
вуглецеву нанотрубку (8, 0) та отримано повну та парцiальну густини станiв цих структур. Показано, що
B i N легованi вуглецевi нанотрубки можуть бути використанi в якостi датчикiв токсичних газiв для таких
молекул як CO, NO, Cl₂ i H₂S.